A Mixed Fullerene-Ferrocene Thermotropic Liquid Crystal: Synthesis, Liquid-Crystalline Properties, Supramolecular Organization and Photoinduced Electron Transfer - Even, Michaël; Heinrich, Benoît; Guillon, Daniel; Guldi, Dirk M.; Prato, Maurizio; Deschenaux, Robert (My University, 2001)
Grafting of a ferrocene-containing liquid-crystalline malonate derivative to C60 led to the mixed fullerene-ferrocene material 1 which gave rise to a smectic A phase. Cholesterol was used as liquid-crystalline promoter. X-ray diffraction experiments and volumetric measurements indicated that 1 is organized in double layered structures. The corresponding supramolecular organization within the mesomorphic lamellar phase is characterized by a microsegregation of the different units (ferrocene, fullerene, and cholesterol) in distinct sublayers. In such a smectic A phase, C60 imposes the arrangement of the other molecular moieties. Photophysical studies revealed that electron transfer occurs from the donor ferrocene to the electron accepting fullerene. The formation of a long-lived radical pair, with lifetimes of the order of several hundred nanoseconds, was confirmed by time-resolved spectrometry, especially in the near infrared region, in which the radical anion of the fullerene moiety displays its characteristic fingerprint absorption.
Keywords: electron transfer; ferrocene; fullerenes; liquid crystals; materials science